New destruxins from the marine-derived fungus Beauveria felina - Lira, Simone P.; Vita-Marques, Aline M.; Seleghim, Mirna H. R.; Bugni, Tim S.; LaBarbera, Daniel V.; Sette, Lara D.; Sponchiado, Sandra Regina Pombeiro [UNESP]; Ireland, Chris M.; Berlinck, Roberto G. S. (Springer Nature, 2006)
Chemical investigation of the cytotoxic and anti-tuberculosis active butanone extract obtained from the growth media of the marine-derived fungus Beauveria felina led to the isolation of two new destruxins, [β-MePro] destruxin E chlorohydrin (1) and pseudodestruxin C (3), along with five known cyclic depsipeptides. The structures of the new destruxin derivatives were established by analysis of spectroscopic data, while the absolute configuration of the common amino acid residues was established by Marfey's analysis. The absolute configuration of the 2(A),4(5)-5-chloro-2,4-dihydroxypentanoic acid residue in 1 could be established by application of a J-based configuration method followed by derivatization with R-MPA-Cl and NMR analysis. © Japan Antibiotics Research Association.
Keywords: Beauveria felina; Destruxins; Fungi; Marine microorganisms; 2,4 5 chloro 2,4 dihydroxypentanoic acid; beta methylprolyldestruxin e chlorohydrin; cyclodepsipeptide; destruxin; destruxin e chlorohydrin; isariin b; phenylalanyl, n methylvalyldestruxin b; pseudodestruxin c; roseocardin; roseotoxin b; unclassified drug; valeric acid derivative; animal cell; antibacterial activity; Beauveria; cancer cell culture; controlled study; cytotoxicity; derivatization; drug isolation; fungus; high performance liquid chromatography; human; human cell; hydrolysis; mouse; nonhuman; priority journal; proton nuclear magnetic resonance; spectroscopy; stereochemistry; Amino Acids; Animals; Antibiotics, Antineoplastic; Antibiotics, Antitubercular; Cell Line, Tumor; Depsipeptides; Fungal Proteins; Humans; Mice; Molecular Structure; Mycobacterium tuberculosis; Mycotoxins; Spectrum Analysis